Operational Speed Analysis of LRT Trains on Curved Track Sections in the Kuningan Line (Long Spans) - Yuli Sulistiyohadi; Alizar Alizar; Norfi Janoko Sakti (International Journal Multidisciplinary Science, 2025)
Mass transit systems such as Light Rail Transit (LRT) offer an efficient and environmentally friendly solution to urban mobility challenges. The performance of LRT systems is highly influenced by track geometric design, particularly in segments involving curve radii and long-span structures. The analysis is based on technical parameters such as centrifugal force, track elevation (superelevation), and railway geometric standards as stipulated by national regulations. The findings indicate a reduction in operational speed on certain curved sections where the radius does not align with ideal design speeds, primarily due to geometric constraints and safety considerations.